Inhibitors and drivers of intention to purchase airline e-tickets in Malaysia - Lee, Kwee Fah (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
The objective of this study is to investigate the determining factors of consumer intention to purchase air tickets online. E-ticketing is a very effective way of cutting costs for the airline industry as this distribution method bypasses travel agents, hence avoiding hefty commission payouts, and airline companies can minimize ticket sales through traditional sales offices which incur large overhead costs. To encourage more consumers to purchase air tickets online, it is important to investigate their purchase intention, which is represented as the dependent variable in this study. Consequently, purchase intention is the primary construct in the research framework. Other factors which determine purchase intention are represented as the constructs of perceived risk (PR), information search (IS), perceived ease of use (PEOU), and perceived usefulness (PU). These constructs were chosen as they comprise of elements that both inhibit and drive purchase intention, a combination of forces that ultimately impact consumer intention to purchase air tickets online. Founded on the theory of perceived risk and Technology Acceptance Model (TAM), the main hypotheses tested were: PR is negatively related to intention to purchase air tickets online, and PEOU as well as PU are each positively related to intention to purchase air tickets online. In addition, the effect of the risk-reliever used by consumers, IS, was also tested in terms of its relationship with PR, and intention to purchase air tickets online. The research method used is the quantitative approach based on the positivist paradigm. Self-administered questionnaires were utilised for online data collection. After screening, the data for 231 sample respondents was analysed for descriptive analyses, followed by PLS-SEM to validate the measures developed for this study and to test the hypotheses. Results of the current study indicate that PR of the internet is the main determinant of intention to purchase air tickets online. PR is influenced by PEOU followed by IS. Moreover, PR comprise of financial, performance, psychological, security and privacy risks, which are separately considered by consumers in purchase decisions. PU is the second most important predictor of intention, and fully mediates the relationship between PEOU and intention. PEOU has no direct effect on intention, indicating ease of internet usage itself has no impact on intention to book flights online. Ease-of-use is only important if online booking is also perceived as useful. Surprisingly, IS does not directly predict intention to purchase air tickets online. Nevertheless, PR acts as a full mediator between IS and intention, hence supporting the risk-reliever role played by information search behaviour. Similar to many past studies, PR and PU have been found to be unrelated to each other. This finding implies that risk and usefulness of the internet are considered to be two separately important determinants of intention to purchase air tickets online. This study is significant because it expands on the theory of perceived risk through the conceptualization of perceived risk from a multidimensional perspective from which the individual dimensions are propounded to form an overall perception of risk; the inclusion of information search as a risk-reliever; as well as the integration with important TAM variables, PEOU and PU in the research model. For practitioners, the findings will guide the development of effective strategies to overcome consumer perceived risk, as well as to promote PEOU and PU, to increase consumer intention to purchase air tickets online.